Thermoelectric properties of a quantum dot attached to normal metal and topological superconductor - Piotr Trocha; Thibaut Jonckheere; Jérôme Rech; Thierry Martin (Scientific Reports)
Abstract The thermoelectric properties of hybrid systems based on a single-level quantum dot coupled to a normal-metal/half-metallic lead and attached to a topological superconductor wire are investigated. The topological superconductor wire is modeled by a spinless p-wave superconductor which hosts both a Majorana bound state at its extremity and above gap quasiparticle excitations. The main interest of our investigation is to study the interplay of sub-gap and single-particle tunneling processes and their contributions to the thermoelectric response of the considered system. The above gap tunneling driven by a temperature gradient is responsible for relatively large thermopower, whereas sub-gap processes only indirectly influence the thermoelectric response. The thermoelectric coefficients, including electric conductance, Seebeck coefficient (thermopower), heat conductance, and figure of merit, are calculated by means of the non-equilibrium Green’s function technique and the temperature dependence of the superconducting gap is considered within the BCS theory. We also consider the system out of equilibrium working as a heat engine. The output power and the corresponding efficiency are presented. Interestingly, under certain conditions, it is possible to extract more power in the superconducting phase than in the normal phase, with comparable efficiency.